Effect of lifestyle intervention on HbA1c levels in overweight and obese adults with type 2 diabetes across ethnicities: A systematic review and meta-analysis of randomized controlled trials - Jie, Yang (2023)
AimsWeight reduction is fundamental for the management and remission of diabetes. We aimed to assess ethnic differences in the effects of lifestyle weight-loss interventions on HbA1c levels in overweight or obese adults with type 2 diabetes mellitus (T2DM). MethodsWe systematically searched PubMed/MEDLINE and Web of Science online databases up to 31 Dec 2022. Randomized controlled trials using lifestyle weight-loss interventions in overweight or obese adults with T2DM were selected. We performed subgroup analyses to explore the heterogeneity across different ethnicities (Asians, White/Caucasians, Black/Africans and Hispanics). A random effects model was applied to calculate weighted mean difference (WMD) with 95% confidence interval (CI). ResultsThirty studies including 7580 subjects from different ethnicities were identified according to the predefined inclusion and exclusion criteria. HbA1c levels were significantly reduced by lifestyle weight-loss intervention. Notably, a significantly beneficial effect on HbA1c was observed in White/Caucasians (WMD = -0.59, 95% CI: −0.90, −0.28, P < 0.001) and Asians (WMD = -0.48, 95% CI: −0.63, −0.33, P < 0.001), but not in the Black/African or Hispanic group (both P > 0.05). The findings remained essentially unchanged in the sensitivity analysis. ConclusionsLifestyle weight-loss interventions had distinct beneficial effects on HbA1c levels in different ethnic groups with T2DM, especially in Caucasians and Asians.